PENGARUH MOTIVASI KERJA DAN PELATIHAN TERHADAP KOMITMEN DALAM MENINGKATKAN KINERJA TENAGA ADMINISTRASI SEKOLAH SMK NEGERI 4 PROBOLINGGO - Sri Utami (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
The research aims to determine the direct and indirect effects of motivation and training on commitment to improve the performance of school administration staff at SMK Negeri 4 Probolinggo. This research is a quantitative study. The number of study samples is the same as the study population of 31 school administration staff. This research was conducted from August 2022 – November 2022.The results of this study are motivation and training variables have a significant effect on commitment. With high motivation and participation in training will increase a strong commitment to the school. The variables of motivation and training have a significant influence on the performance of school administration staff, with high motivation and participation in training increasing performance as a measure of an employee's ability. However, the training variable partially does not affect performance. The commitment variable has a significant influence on the performance of school administrative staff, this shows that commitment can improve the performance of school administrative staff.The variables of motivation and training together have a significant influence on the performance of school administration staff with commitment as an intervening variable, because the direct coefficient value between motivation and training is greater than the indirect effect through the commitment variable, so the mediating influence is weak on performance.